2008
DOI: 10.1017/s0007114508981411
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gene expression profiles in juvenile rainbow trout (Oncorhynchus mykiss) fed fishmeal or fish oil-free diets

Abstract: Reducing the reliance on fishery by-products as amino acid and fatty acid sources in feeds for farmed fish is a major objective today. We evaluated the effect of dietary fish oil or dietary fishmeal replacement by vegetable oils and plant proteins respectively through analysis of hepatic transcriptomes in rainbow trout (Oncorhynchus mykiss). Fish were fed right from first feeding with diets based on plant by-products before being killed. We analysed the hepatic gene profile using trout cDNA microarrays (9K). O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
61
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 46 publications
(67 reference statements)
13
61
3
6
Order By: Relevance
“…As a consequence, metabolic changes associated with inflammatory processes and infectious diseases can modify protein and AA requirements. Similarly, the recent introduction of genomic and post-transcriptomics tools are greatly contributing to a better understanding of the metabolic pathways affected by changes in the dietary protein quality (e.g., Martin et al 2003;Vilhelmsson et al 2004;Sitjà-Bobadilla et al 2005;Panserat et al 2008). In brief, such studies highlighted a number of metabolic pathways sensitive to plant-protein feeding in several fish species, for example, pathways involved in cellular protein degradation, fatty acid breakdown, NADPH metabolism and the expression of heat-shock proteins, which could be indicative of a stress/immune-mediated response.…”
Section: Plant Protein Sources Antinutritional Factors and Fish Welfarementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, metabolic changes associated with inflammatory processes and infectious diseases can modify protein and AA requirements. Similarly, the recent introduction of genomic and post-transcriptomics tools are greatly contributing to a better understanding of the metabolic pathways affected by changes in the dietary protein quality (e.g., Martin et al 2003;Vilhelmsson et al 2004;Sitjà-Bobadilla et al 2005;Panserat et al 2008). In brief, such studies highlighted a number of metabolic pathways sensitive to plant-protein feeding in several fish species, for example, pathways involved in cellular protein degradation, fatty acid breakdown, NADPH metabolism and the expression of heat-shock proteins, which could be indicative of a stress/immune-mediated response.…”
Section: Plant Protein Sources Antinutritional Factors and Fish Welfarementioning
confidence: 99%
“…The specific effects of individual ANFs as modulators of fish welfare status are scarcely known. Despite scarce, species-specific and conditioned by fish size, studies have associated the dietary levels of ANFs to: (1) Disturbances on the absorption of nutrients through the inhibition of digestive enzymes by protease inhibitors (Krogdahl et al 1994;Santigosa et al 2008), alterations in digesta viscosity and consequently of feed transit time and binding of bile salts in the gut by carbohydrate fractions (Refstie et al 1999;Leenhouwers et al 2007), chelating effect of phytic acid forming protein and mineral complexes (Vielma et al 2004); (2) Alteration in metabolic pathways, namely in relation to protein and AA metabolism (Martin et al 2003;Panserat et al 2008), primary energy metabolism (production of NADPH, ATP) (Vilhelmsson et al 2004), somatotropic axis (Gómez-Requeni et al 2004); (3) quantitative and qualitative changes in intestinal microflora (Refstie et al 2006); (4) Inflammatory and histopathological lesions in the gastrointestinal tract (Urán et al 2008); and (5) activation of non-specific immune response, stress indicators and oxidative status (Rumsey et al 1994;Sitjà-Bobadilla et al 2005). The full nature of ANFs effects in fish clearly requires further research.…”
Section: Plant Protein Sources Antinutritional Factors and Fish Welfarementioning
confidence: 99%
“…It is known that the composition of the diet, and particularly dietary lipids, can influence the endocrine system and alter the expression of genes of the somatotropic axis (Benedito-Palos et al, 2007;Cameron et al, 2007). But most of the studies on the influence of nutrition in teleost gene expression have focused on the type of amino acids and fatty acids or on the fast and refeeding regimes (Benedito-Palos et al, 2007;Bower et al, 2008;Chauvigné et al, 2003;Hagen et al, 2009;Johansen and Overturf, 2006;Montserrat et al, 2007;Panserat et al, 2008;Rescan et al, 2007), and there is little or no knowledge on the effects of different dietary lipid contents in the regulation of growth genes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to changes in genes involved in lipogenesis, complete fish oil replacement caused changes in the hepatic expression of genes involved in steroid synthesis, xenobiotic detoxification, protein catabolism and transcriptional regulation, interestingly in the absence of changes in body weight, feed efficiency and feed intake (Panserat et al 2008a,b). In contrast, replacement of animal proteins (fish meal) with plant proteins in the diet caused a reduction of growth rates and feed efficiency and increased feed intake in rainbow trout, which was accompanied by altered expression of genes involved in protein and amino acid metabolism (Panserat et al 2008b). Not surprisingly, similar changes were observed in the liver of rainbow trout after a 3-week fasting period: decreased expression of genes involved in protein biosynthesis and increase in the machinery needed for protein degradation (Salem et al 2007).…”
Section: Transcriptional Changes In the Liver In Relation To Growth Amentioning
confidence: 98%
“…These observations suggested that these fish, as a result of their nutritional challenge, decreased their capacity for β-oxidation in the liver. More recently, fish oil replacement (100%) with vegetable oil for 62 weeks from first feeding in rainbow trout has also been shown to decrease the expression of two genes involved in lipid metabolism: fatty acid synthase and long-chain fatty acid elongase (Panserat et al 2008b). In addition to changes in genes involved in lipogenesis, complete fish oil replacement caused changes in the hepatic expression of genes involved in steroid synthesis, xenobiotic detoxification, protein catabolism and transcriptional regulation, interestingly in the absence of changes in body weight, feed efficiency and feed intake (Panserat et al 2008a,b).…”
Section: Transcriptional Changes In the Liver In Relation To Growth Amentioning
confidence: 99%